Trends in COVID-19-associated mortality in patients with pulmonary hypertension: a COMPERA analysis. Issue 4 (27th April 2023) - Schmidt, Kai-Helge; Milger, Katrin; Pausch, Christine; Huscher, Doerte; Pittrow, David; Grünig, Ekkehard; Staehler, Gerd; Gall, Henning; Distler, Oliver; Skowasch, Dirk; Halank, Michael; Wilkens, Heinrike; et al.
Patients with pulmonary hypertension (PH) have been among those affected heavily by the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Early case series reported case fatality rates ranging from 19–45% in small series of 11–70 patients with PH who contracted COVID-19 [1–4]. A prospective series of 211 French patients with various forms of PH, who developed COVID-19 between February 2020 and April 2021, found an overall case fatality rate of 24.6% [5]. In patients with pulmonary hypertension, the mortality rate associated with COVID-19 has declined sharply with the emergence of the Omicron variants https://bit.ly/42OMsfj